miRNAs are necessary for vascular smooth muscle growth, differentiation and function - Albinsson, Sebastian (2010)
OBJECTIVE: Regulation of vascular smooth muscle (VSM) proliferation and contractile differentiation are important factors in vascular development and subsequent cardiovascular diseases. Recently, microRNAs (miRNAs) have been shown to regulate fundamental cellular processes in a number of cell types but the integrated role of miRNAs in VSM in blood vessels is unknown. Here, we investigated the role of miRNAs in VSM by deleting the rate limiting enzyme in miRNA synthesis, Dicer. METHODS AND RESULTS: Deletion of Dicer in VSM results in late embryonic lethality at E16-E17 associated with extensive internal hemorrhage. The loss of VSM Dicer results in dilated, thin walled blood vessels caused by a reduction in cellular proliferation. In addition, blood vessels from VSM deleted Dicer mice exhibited impaired contractility due to a loss of contractile protein markers. We found this effect to be associated with a loss of actin stress fibers, and partly rescued by over expression of miR-145 or myocardin. CONCLUSION: Dicer-dependent miRNAs are important for VSM development and function by regulating proliferation and contractile differentiation.